Exploring accessibility conditions for bike–train commuting: A qualitative study among university staff in Belgium - Rybels, Stijn; Vanoutrive, Thomas (European Journal of Transport and Infrastructure Research, 2026)
The integration of cycling and rail transport is a key element of sustainable commuting, yet its success depends on the accessibility of stations, their surrounding environments, and destinations. While quantitative studies have extensively analysed infrastructural and behavioural determinants of bike–train use, fewer have examined how users perceive accessibility in practice. This article explores how accessibility conditions shape the bike–train commuting experience in Flanders, Belgium. Drawing on five focus groups with university staff across four campuses with varying levels of bike–train accessibility, the analysis identifies critical accessibility dimensions at both the home-end and activity-end of trips. Physical accessibility factors, including bicycle parking availability, visibility and proximity to platforms, strongly shape users’ evaluations of station quality. Accessibility is further influenced by the presence of cycle highways, multiple station entrances, and the availability and coverage of shared bicycle systems. Beyond physical elements, perceived accessibility is affected by train frequency and reliability, ease of use, perceived safety, legibility and design of the public realm, and the atmosphere and services provided at stations. The findings demonstrate that accessibility challenges and expectations differ substantially between home-end and activity-end stations: the former is primarily evaluated based on functional access to platforms, while the latter is judged more broadly on service reliability and the comfort of the station environment. While limited to current users, this study offers qualitative evidence on how accessibility conditions shape the usability of bike–train commuting, informing policies aimed at strengthening multimodal integration.